The Spontaneous Deposition of Au on Pt (111) and Polycrystalline Pt. Issue 12 (1st January 2016) - Ambrozik, Stephen; Mitchell, Corey; Dimitrov, Nikolay
Abstract : Gold is epitaxially grown by spontaneous deposition (SD) on Pt(111) and Pt[poly]. It has been demonstrated that in the system of interest the SD takes place as a hybrid process, consisting of the potential-controlled reduction of an adsorbed [AuCl4 ] − complex along with an electroless reduction of the same complex coupled with Pt surface oxidation over the course of adsorption. This hybrid deposition process is shown to promote an outstanding layer-by-layer growth mode on Pt(111) that involves the formation of smooth films with virtually no surface roughness increase. This finding is seconded by in-situ STM experiments demonstrating that the SD of Au on Au(111) leads to similar growth results. In addition, an adlattice structure of 7 × 7 r19.1° is determined for the [AuCl4 ] − adsorbate on Au (111) suggesting a theoretical deposited amount of about 15% Au surface coverage per SD cycle. It has been shown that a Pt(111) substrate is completely masked after five cycles of SD followed by layer densification in continuity development. It has also been shown that the Au amount deposited specifically through the electroless route can be controlled by the amount of initial Pt oxidation, the concentration of dissolved O2, and the duration of [AuCl4 ] − adsorption process.